2011
DOI: 10.1108/08876041111173642
|View full text |Cite
|
Sign up to set email alerts
|

How brand innovativeness and quality impact attitude toward new service line extensions: the moderating role of consumer involvement

Abstract: PurposeThe purpose of this study is twofold: first, to assess the impact of extension innovativeness on attitude towards service line extension and the mediating role played by extension quality (in relation to the parent brand); second, to examine the effect of consumer involvement as a moderator of the relationship between extension quality (in relation to the parent brand) and attitude towards the extension.Design/methodology/approachAn empirical investigation using a survey methodology was conducted with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 93 publications
(104 reference statements)
2
46
1
2
Order By: Relevance
“…Our results are in line with those of Martínez and Pina (2010) who found that familiarity had no significant effect on extension attitude. Boisvert and Ashill (2011) The data also suggest that the individual's perception of trust in the retailer's ability to provide the new service is a determining factor, as it is the one that most directly affects the likelihood of him/her purchasing the new SB travel service. Therefore, individuals who are highly familiar with products under the store's own brand (SB) currently offered by the retailer, may tend to encase the retailer's SB in those categories, thereby hindering a broader perception of possible new products/services under the SB.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with those of Martínez and Pina (2010) who found that familiarity had no significant effect on extension attitude. Boisvert and Ashill (2011) The data also suggest that the individual's perception of trust in the retailer's ability to provide the new service is a determining factor, as it is the one that most directly affects the likelihood of him/her purchasing the new SB travel service. Therefore, individuals who are highly familiar with products under the store's own brand (SB) currently offered by the retailer, may tend to encase the retailer's SB in those categories, thereby hindering a broader perception of possible new products/services under the SB.…”
Section: Resultsmentioning
confidence: 93%
“…Although, as already noted, retailers have extended their store brands (SB) to travel services, the limited amount of specialized literature dealing with the factors that bear upon the acceptance of such extended SB services (Boisvert and Ashill 2011;Laforet 2007;Zboja and Voorhees 2006), and in particular travel services, is nevertheless surprising.…”
Section: Discussion and Implications For Nbs And Plsmentioning
confidence: 99%
“…ProInv refers to the general level of interest or concern with regard to a product class (Suh & Youjae, 2006). ProInv can also be defined as the perceived relevance of the product based on inherent needs, values, and interests (Boisvert & Ashill, 2011). The impact of communicating FFIWeb on consumer response can be moderated by the level of consumers' product involvement.…”
Section: The Moderating Role Of Proinvmentioning
confidence: 99%
“…Recent studies show that product innovativeness enhances customers' perception of brand innovativeness (e.g. Boisvert and Ashill 2011;Schreir et al 2012;Rubera and Kirca 2012), and that there is a spill-over effect from 'flagship' products on brand innovativeness (Hubert et al 2017).…”
Section: Product/brand Innovativenessmentioning
confidence: 99%
“…Goldsmith et al 1998;Im et al 2003;Im et al 2007;Truong 2013), brand innovativeness (e.g. Alam and Perry 2002;Boisvert and Ashill 2011), and supplier innovativeness (Choi and Krause 2006;Inemek and Matthyssens 2013). Other types of innovativeness related to marketing include organisational (e.g.…”
Section: Introductionmentioning
confidence: 99%